On stability of solutions to parametric generalized affine variational inequalities. (1st February 2018) - Nghi, Tran Van
Abstract: This paper deals with the stability of the solution set to parametric generalized affine variational inequalities with constraint set being defined by finitely many convex quadratic functions. The obtained results develop and complement the published ones.